THE INTEGRATION OF WAHDATUL 'ULUM VALUES IN THE SOCIO-RELIGIOUS LIFE OF INDONESIAN MUSLIMS - Rini Susilowati; Acep Nurullah (Karimiyah: Journal of Islamic Literature and Muslim Society, 2026)
This study examines the integration of Wahdatul 'Ulum values the unity of knowledge paradigm developed at UIN Sumatera Utara into the socio-religious life of Indonesian Muslims. Employing a qualitative approach grounded in social-religious hermeneutics, the research draws on participatory observation, in-depth interviews, and documentary analysis to reveal how integrative epistemological values are interpreted, negotiated, and embodied across diverse domains of Muslim practice. The study identifies seven principal manifestations of Wahdatul 'Ulum in Indonesian Muslim life: integrative Islamic higher education, tawhid-based Arabic language learning, Islamic communication and broadcasting, value-based leadership, Islamic healthy lifestyle promotion, halal supply chain management, and the religious moderation discourse. Findings demonstrate that the knowledge dichotomy inherited from the Dutch colonial era produced a dual epistemological crisis that Wahdatul 'Ulum systematically addresses through tawhidic ontology, positioning revelation and reason as complementary rather than hierarchical. The paradigm exhibits a deep epistemological convergence with the national wasatiyyah agenda, functioning as an epistemological vaccine against radicalism by cultivating holistic, multi-perspective critical thinking among students and communities. Islamic organizations particularly Nahdlatul Ulama and Muhammadiyah alongside pesantren and digital da'wah platforms serve as key agents amplifying the paradigm's reach beyond formal educational settings. Implementation challenges include the absence of operationally robust integration methodology, institutional resistance, resource constraints, and inadequate evaluation instruments. The study concludes that Wahdatul 'Ulum constitutes a strategic intellectual asset for Indonesia's religious moderation agenda and recommends comprehensive policy integration across education, the halal industry, and interfaith governance as a basis for future research and reform.